Transformation of Communication Practices in Visual Radio: A Case Study of Gaul FM Semarang - Mohammad Ismed; Imanuel Ronald David Mongkau; Ummy Hanifah (Prodi Ilmu Komunikasi UTM, 2026)
The advancement of digital media has encouraged radio broadcasters to adopt **visual radio** as an adaptive response to changing audience behavior and the evolving digital communication ecosystem. This study examines the transformation of communication practices at Visual Radio Gaul FM Semarang and its implications for broadcaster–audience relationships. A qualitative single-case study design was employed. Data were collected from January to March 2025 through observations of visual broadcasting practices, documentation of digital content, and analysis of Gaul FM Semarang’s publication materials. The study involved five categories of informants: broadcasters, a station manager, active digital audiences, social media administrators, and intern students. Data were analyzed using an established six-phase thematic analysis procedure. The findings indicate that visual radio extends beyond changes in broadcast distribution by restructuring communication practices through real-time interaction, greater audience participation, and the transformation of broadcasters from one-way communicators into facilitators of digital dialogue. This study contributes to media communication scholarship by demonstrating that visual radio represents a restructuring of communication practices that strengthens the audience’s role as an active communication partner within the digital media ecosystem.